Application Of Criminal Law Against Corporations For Criminal Actions Of Tax Evavasion Based On Law Of The Republic Of Indonesia Number 28 Of 2007 Concerning General Provisions And Procedures For Taxation - Ismaidar Ismaidar; T. Riza Zarzani; Muhammad Faiz Hadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Constitutionally, tax collection is regulated in Article 23A of the 1945 Constitution of the Republic of Indonesia which confirms that taxes and other coercive levies are for state needs as regulated by law. Tax regulations themselves are regulated in Law of the Republic of Indonesia Number 28 of 2007 concerning General Provisions and Tax Procedures. Tax is an official state levy on taxpayer citizens. What is meant by taxpayer is an individual or entity including taxpayers, tax holding agents and tax collectors who have tax rights and obligations in accordance with the provisions of tax laws and regulations. As time goes by and the development of economic globalization, there is a lot of potential for crimes or crimes in the economic sector committed by corporate business actors. The difficulty of holding corporations criminally liable results in many material and immaterial losses to the state. However, criminal liability in the form of strict liability can provide a solution to this problem. Where full corporate criminal liability (strict liability) states that corporations can be held criminally liable. This research uses normative research methods by taking a statutory approach and a conceptual approach. The data obtained in this research was through literature study by collecting data from secondary legal materials, namely primary data, secondary data and tertiary data related to the problem formulations that will be discussed in this research. Then the data obtained is analyzed and described qualitatively. The aim of this research is to determine the modus operandi of perpetrators in committing criminal acts of tax evasion based on Law of the Republic of Indonesia Number 28 of 2007 concerning General Provisions and Tax Procedures and to find out how criminal law is applied to corporations for criminal acts of tax evasion based on Law of the Republic of Indonesia Number 28 of 2007 concerning General Provisions and Tax Procedures.